The Effect of the Scratch Application on Students' Learning Motivation and Computational Thinking Skills - Ifan Habibi, Sucipto, Sri Yuni Hanifah (Lembaga Bale Literasi, 2025)
Students are required to be proficient in computational thinking and increase their learning motivation starting from middle school due to advancements in digital technology. 21st-century skill needs and teaching methods continue to differ, especially in terms of incorporating technology that facilitates systematic problem-solving. The Starch app is relevant for honing these skills because it offers interactive elements for practicing decomposition, pattern recognition, abstraction, and algorithms. This research aims to investigate the effects of the Scratch program on the computational thinking abilities and learning motivation of junior high school pupils. In a real experiment using a pretest-posttest control group design, 35 eighth graders were put through a quantitative procedure, with 18 students serving as the experimental group and 17 students as the control group. To create expert-verified tests, we use the Computational Thinking Framework Indicators as our foundation. When analysing the data, independent t-tests are used. A t-test significance value of 0.003 < 0.05 and computational thinking ability of 0.000 < 0.05 indicate that the experimental group exhibited a notable rise in learning motivation, according to the study findings. This research demonstrates the successful integration of the Scratch application into learning to simultaneously enhance learning motivation and computational thinking skills, while also meeting the digital literacy needs of junior high school students in the 21st century, it also serves as a reference for teachers and schools in integrating educational technology into the learning process.